LISTENING AND SPEAKING IN THE EXTENSIVE ENGLISH COURSE: INSIGHTS FROM A POSTGRADUATE EFL CONTEXT - Susanti, Aam Eka; Handayani, Reli; Haryanto, Eddy (Jurnal Ilmiah Bina Bahasa, 2025)
This study aimed to understand the perspectives of graduate participants on the learning of listening and speaking skills during the Extensive English courses within the English Education Master’s Program at the University of Jambi. A qualitative descriptive method was employed, using brief, focused open-ended interviews with nine respondents after completing the course. Their responses were thematically analyzed to identify emerging perceptions, learning experiences, and factors that influenced the learning process both constructively and otherwise. The results indicate that participants thrive in supportive, motivating environments that foster interaction and communication. They valued the use of authentic learning materials—particularly videos, podcasts, and other digital resources—which enhanced motivation, confidence, active participation, and engagement. Constructive criticism was recognized as a motivational factor that encouraged language development and self-directed learning. However, some respondents suggested a better balance between material difficulty and time allocated to speaking practice. These findings indicate that while the provision of authentic materials and a supportive pedagogical approach contributed significantly to students’ improvement, the course’s greater strength lies in how these elements fostered learner autonomy and self-confidence—key factors in sustaining long-term oral communication development.